Insiden Syok Neurogenik pada Pasien dengan Cedera Tulang Belakang - Shaleh, Humairah; Rachman, Moch Erwin; Wisudawan, Wisudawan; Muchsin, Achmad Harun; Maricar, Fadillah (Rumah Sakit Ibnu Sina, Makassar, 2023)
Neurogenic shock is mostly associated with cervical and thoracic spine injuries. Neurogenic shock after complete spinal cord injury is difficult to treat and the prognosis remains severe most of the time. Research objectives iThis is to find out the incidence of neurogenic shock in patients with spinal cord injuries based on the location of the injury and the patient's mortality.This type of research uses the methodnarrative reviewand data collection was carried out from several literatures in accredited international journals. The results showed that neurogenic shock was 13.0% in living patients and 38.0% of patients who died after experiencing traumatic spinal cord injury and the incidence of neurogenic shock based on the location of the injury, Ruiz et al., in Canada as much as 29.1% cervical 18.5% thoracic. Wechtet al., in the United States as many as 38.7% cervical, 22.2% high thoracic, 22.7% low thoracic. Gulyet al., in England, 19.3% cervical, 7.0% thoracic, 3.0% lumbar. Ravensbergenet al., in the Netherlands as much as 45.6% cervical, 26.3% thoracic, 23.8% lumbar. Katzelnicket al., in the United States, as many as 11% cervical, 8% high thoracic, 0% low thoracic. Based on the results of a review of some of the literature, it can be concluded that the incidence of neurogenic shock in patients with spinal cord injuries based on the location of the injury was mostly at the cervical level and based on the patient's mortality status, it was found that more patients died after experiencing traumatic spinal cord injury.